Standardization of the normative group for the third version of the test of visual attention - TAVIS - Coutinho,Gabriel (2008)
Abstract Despite the importance of objective measures of attention to clinical practice, there is a paucity of Brazilian standardized tests. Objective: The aim of the present study was the standardization of a normative group for the third version of a computerized test of visual attention (TAVIS-3), developed to evaluate children and adolescents in the 6 to 17 years age range. Methods: 631 students from 3 schools in Rio de Janeiro city were assessed with TAVIS-3, administered by experienced psychologists, following parents' authorization. Results: The normative groups were determined considering performance of different age groups: from 6 to 10 years (with scores for 5 different ages); from 11 to 12 and from 13 to 17 years. Three tasks (focused, shifted and sustained attention) were standardized for each age group. Conclusion: The standardization of a normative group for TAVIS-3 discriminated performance ranges for distinct age groups, allowing its use as a neuropsychological assessment of attention.